Skin antiseptic choice to reduce catheter-related bloodstream infections - Lily Rundjan (Indonesian Pediatric Society, 2011)
Background The use of vascular access devices (VADs) may put patients at risk for bloodstream infections. Despite infection control prevention methods used in our neonatal unit, mean catheter-related blood stream infection (CRBSI) rates are quite high. One contributing factor for these high infection rates may be the skin antiseptic preparation procedure undertaken prior to intravenous line insertion.Objectives We aimed to reduce CRBRBSI rates by changing to octenidine hydrochloride antiseptic solutions for skin preparation in the neonatal unit at Cipto Mangunkusumo Hospital.Methods Antiseptics for skin preparation were changed from povidone-iodine or alcohol to octenidine hydrochloride from September to November 2010. Bloodstream infection rates and hand hygiene compliance were recorded and compared before and during the study.Results The mean CRBRBSI rate in the neonatal unit before changing the skin antiseptic solution (January – August 2010) was 11.68‰ (‰ means per 1000 patient-days). During the study, CRBSI rates decreased significantly to 1.1‰ in the first month, increased to 8.7‰ in the second month, and decreased to 2.4‰ in the third month. Hand hygiene compliance for 1 moment (before aseptic task) fluctuated, reaching 93.8% and 100% before and during the study, respectively. Compliance for the remaining 4 moments of hand hygiene as defined by the World Health Organization (WHO), ranged from 33.0 – 87.3% before the study and 8.0 – 100.0% during the study. The most striking decrease in these 4 moments of hand hygiene compliance in the second month was accompanied by a marked increase in CRB SI rate.Conclusions Reduced CRB SI rates cannot be attained by solely changing antiseptic solutions for skin preparation. Maintaining other prevention strategies, such as adhering to the 5 moments of hand hygiene recommended by WHO is also very important.